Assess Knowledge and Attitudes on First-Aid Measures for Selected Domestic Accidents among Caretakers of Under-Five Children (Medico Legal Update, 2021)
Background: Mishaps are one of the fifth driving reasons for death in industrialized and creating nations.Wounds emerging from mishaps are an expanding general medical issue. Mishaps are a noteworthy reasonfor dreariness and mortality in kids.Objectives: The present study was undertaken to find out the knowledge level of women regarding domesticaccidents among children.Method: A descriptive comparative research design was used for the present study. A study sample of 100care takers of under- five children (50 residing in rural area and 50 residing in urban area) were selected withhelp of purposive sampling method. Structured questionnaire was used to assess the knowledge and Likertscale was used to find out the attitude regarding first aid measures regarding selected domestic accidentsamong under five children.Results: In rural area maximum numbers of care takers had average knowledge regarding domestic accidentsi.e. 74%, 22% had good knowledge and 4% had below average. Where as in urban area maximum numbersof care takers had average knowledge regarding domestic accidents i.e. 62%, 33% had good knowledge and8% had below average. In rural area maximum numbers of care takers had undecided attitude regardingdomestic accidents i.e. 64%, 36% had strongly disagree attitude and 0% had strongly agree attitude regardingstatements. Where as in urban area maximum numbers of care takers had undecided attitude regardingdomestic accidents i.e. 78%, 20% had strongly disagree attitude and 2% had strongly agree attitude regardingstatements.Conclusion: The study findings concluded that majority of care takers have average knowledge and undecidedattitude towards domestic accidents of under five children. So, the researcher provides the informationbooklet to enhance and improve knowledge and attitude of care takers towards domestic accidents.